CO2 dry-reforming of methane over La0.8Sr 0.2Ni0.8M0.2O3 perovskite (M = Bi, Co, Cr, Cu, Fe): Roles of lattice oxygen on C-H activation and carbon suppression - Sutthiumporn, K. (2014)
10.1016/j.ijhydene.2012.04.059